How do you express disappointment with a travel agency? Analysis of comments on the tourist portal Wakacje.pl - Burska, Katarzyna (Papers in Linguistics, 2019)
The aim of this article is to analyse negative comments referring to four travel agencies on the tourism portal Wakacje.pl. Elements subjected to critical evaluation as well as linguistic and para-linguistic methods of presenting disappointment were examined. Internet users express dissatisfaction, above all, with linguistics – especially nouns, as well as adjectives, adverbs and verbs. They often use colloquial Polish. Customers of travel agencies focus not only on their emotions, but they try to inform and discourage others by using advice or warnings.